(untitled) (Nordic Journal of African Studies, 1999)
Although Funmilayo Ransome Kuti (1900-1978) was one of the most important nationalist and feminist figures of Nigeria, it was not until 1997 that a biography of her was published. In this paper, I will examine how she is constructed in the biography For Women and the Nation: Funmilayo Ransome-Kuti of Nigeria by Cheryl Johnson-Odim and Nina Emma Mba. I will also look at her construction in Fela Fela, This bitch of a life, edited by Carlos Moore in 1982. The Yorubas – one of the three biggest ethnic groups of Nigeria – have been divided into a number of groups including the Egbas, to which Funmilayo Ransome-Kuti belonged. Yorubas have been essentially town dwellers (Fadipe 1991: 113), and she was not an exception. To define her local identity even more precisely: she was born in Abeokuta, lived in Abeokuta most of her life and even died there. In this paper I am interested in the construction of Funmilayo Ransome-Kuti through her negotiation of various values in general and deeds of resistance in particular. I will also have a look at the world view of her son Fela Kuti (1938-1987), wishing through comparisons to better characterize the world view of Funmilayo Ransome-Kuti.